EMPOWERING LOCAL GOVERNMENTS: REGIONAL AUTONOMY AS A CATALYST FOR GOOD GOVERNANCE IN INDONESIA - Habibi, Dani (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2025)
Regional autonomy reform in Indonesia is a key initiative aimed at enhancing governance by ensuring greater transparency, accountability, and efficiency in local government operations. By decentralizing authority, local governments gain the freedom to manage regional affairs and develop policies that are more closely aligned with their communities' needs. The ultimate goal of regional autonomy is to improve community welfare by enabling regions to design and implement targeted solutions. However, the process faces several challenges, including disparities in regional development, ineffective resource management, and insufficient coordination between the central and local governments. Addressing these issues requires a transformation in community attitudes, improved government capacity, and enhanced public participation in decision-making. The successful implementation of regional autonomy depends on effective policy reform and better management practices, alongside active involvement from the community. Local wisdom should be integrated into development strategies, ensuring that policies respect and preserve cultural diversity while promoting sustainable growth. Additionally, strengthening oversight mechanisms, improving transparency in budget management, and fostering intergovernmental cooperation are crucial for achieving equitable development outcomes. Regional autonomy reform holds significant potential for creating a more responsive government that better serves its people. However, to unlock this potential, it is essential to build the capacities of local governments, ensure effective supervision, and encourage inclusive decision-making processes. This approach will contribute to the realization of sustainable development goals, fostering a more just, accountable, and efficient governance system.